'We Know in Part': How the Positive Apophaticism of Aquinas Transforms the Negative Theology of Pseudo‐Dionysius. (16th September 2011) - Darley, Alan Philip
Abstract : There has been a new reception and revival of interest in the Pseudo‐Dionysius both in popular and academic circles, which has impacted Thomistic scholarship. Scholars roughly from the time of Vatican II have stressed the importance of Pseudo‐Dionysius to Thomistic thought, in reaction to a previous emphasis on the 'Aristotelian' and analytic aspects of Thomistic thought. Whilst this approach uncovered a largely neglected area, the converse now appears to be the case: the Dionysian influence on Thomas is disproportionately exaggerated, leading to a false identification of the two thinkers. This paper argues that whereas the negative theology of Pseudo‐Dionysius entailed the unknowability of God as the One beyond language, concept and being, Thomas developed a 'positive apophaticism' that transformed Denys in light of Augustine, Aristotle and, most importantly, Scripture itself. I first trace the roots of apophaticism showing how neo‐Platonism leads to equivocal God‐talk and why Aquinas goes further than Dionysius in his rejection of equivocity. I then show how the unknowability of God taught by Dionysius is qualified by Thomas through his teaching on the 'quidditative' knowledge in the next life and through the doctrine of analogy in the present life that makes possible the naming of God using positive 'perfection terms.' The primary perfection term is Being which, in contrast to the Dionysian God 'beyond being, ' applies to God literally and pre‐eminently. This has implications for epistemology since, as Aristotle showed, knowledge and rational discourse are grounded in Being. The reason Denys' theology leads to an absolute unknowing is because He denies that God is identical with Being, whereas Aquinas' metaphysics, while denying univocal being, retains true speech about God, including logical discourse by analogy. I finally explain how in spite of believing Dionysius to be a first century apostolic convert, Thomas was able to transform his teaching because of presuppositions regarding the authority of Scripture that he interprets in light of Augustine, Aristotle and a developing understanding of a 'literal' sense that stands in contrast to the 'anagogical' hermeneutic of Dionysius. This results in an undermining of Dionysian elitism that anticipates the work of the Reformers, beginning with John Wyclif. In the contemporary context, Thomas' 'positive apophaticism' offers a powerful resource for addressing an increasingly agnostic culture.